Living in Flow: The Science of Synchronicity and How Your Choices Shape Your World by Sky Nelson-Isaacs - Rawlette, Sharon Hewitt (Journal of Scientific Exploration, 2019)
While Sky Nelson-Isaacs is not the first physicist to be interested in the phenomenon of synchronicity—others who come to mind are Wolfgang Pauli, F. David Peat, and Walter von Lucadou—Nelson-Isaacs’ new book Living in Flow is notable for its engaging and highly readable presentation of his particular theory about the relationship between quantum physics and synchronicity. Like the great idealist philosophers before him, Nelson-Isaacs takes mind to be the primary reality, and his theory explains how the contents of our minds—in particular, the qualities of the experiences we anticipate having—shape the evolution of the physical world through the process of “meaningful history selection.” Nelson-Isaacs also links his theory to psychologist Mihaly Csikszentmihalyi’s concept of flow, positing that we are best able to shape the evolution of the world in accordance with our desires when we are in the state of flow. Nelson-Isaacs begins his book with the psychological component of his theory and works up to the quantum physics near the end, but I’m going to take the opposite approach here.